Circulating Proprotein Convertase Subtilisin/Kexin type 9 level independently predicts incident cardiovascular events and all-cause mortality in hemodialysis black Africans patients - François-Pantaléon Musungayi Kajingulu; François Bompeka Lepira; Aliocha Natuhoyila Nkodila; Jean-Robert Rissassy Makulo; Vieux Momeme Mokoli; Pepe Mfutu Ekulu; Justine Busanga Bukabau; Yannick Mayamba Nlandu; Augustin Luzayadio Longo; Nazaire Mangani Nseka; Laura Labriola; Ernest Kiswaya Sumaili (BMC Nephrology, 2022)
Abstract Background Cardiovascular (CV) disease is the leading cause of mortality in patients with end-stage kidney disease (ESKD). The aim of the present study was to determine whether Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) could be an independent predictor of CV events and all-cause mortality in black African haemodialysis patients. Methods We carried out a prospective cohort study of all consecutive hemodialysis (HD) patients between August 2016 and July 2020, admitted in six hemodialysis centers of Kinshasa, Democratic Republic of Congo. Independent determinants of plasma PCSK-9 measured by ELISA were sought using multiple linear regression analysis. Kaplan-Meier’s method described the incidence of CV events while competitive and proportional risk models looked for independent risk factors for death at the .05 significance level. Results Out of 207 HD patients, 91 (43.9%) died; 116 (56.1%) have survived. PCSK9 level was significantly higher in deceased patients compared to survivors: 28.0 (24.0–31.0) ng/l vs 9.6 (8.6–11.6) ng/ml (p <  0.001). Patients with plasma PCSK9 levels in tertile 3 had a higher incidence of CV events and mortality compared to patients with plasma PCSK9 levels in tertile 2 or tertile 1 (p <  0.001). Tertile 3 negatively influence survival rates (26.6%) compared to tertile 2 (54.7%) and tertile 1 (85.3%). Patients in tertile 3 and tertile 2 had a 4-fold higher risk of death than patients in tertile 1. After adjustment for all parameters, competitive risk analysis showed that mortality was 2 times higher in patients with stroke. Similarly, serum albumin < 3.5 g/dL or PCSK9 in tertile 3 were respectively associated with 2 or 6 times higher rates of deaths. Conclusion Elevated plasma PCSK9 level is an independent major predictor of incident CV events and all-cause mortality in black African HD patients.